2018
DOI: 10.1117/1.jbo.23.7.075004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating integrin activation with time-resolved flow cytometry

Abstract: Förster resonance energy transfer (FRET) continues to be a useful tool to study movement and interaction between proteins within living cells. When FRET as an optical technique is measured with flow cytometry, conformational changes of proteins can be rapidly measured cell-by-cell for the benefit of screening and profiling. We exploit FRET to study the extent of activation of α4β1 integrin dimers expressed on the surface of leukocytes. The stalk-like transmembrane heterodimers when not active lay bent and upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…The robustness of phasor graphing was demonstrated in a TRFC FRET integrin study where surface integrins varied in their conformational states in the absence and presence of artificial stimuli. The study found the existence of multiple photophysical states of an antigen-conjugated chromophore that were not easily resolved with TRFC alone (see Figure 8) [31]. Phasor analyses can generally improve TRFC data collection and provide a way to statistically map lifetime changes, which is important for many biological applications.…”
Section: Frequency-domain Trfcmentioning
confidence: 99%
See 1 more Smart Citation
“…The robustness of phasor graphing was demonstrated in a TRFC FRET integrin study where surface integrins varied in their conformational states in the absence and presence of artificial stimuli. The study found the existence of multiple photophysical states of an antigen-conjugated chromophore that were not easily resolved with TRFC alone (see Figure 8) [31]. Phasor analyses can generally improve TRFC data collection and provide a way to statistically map lifetime changes, which is important for many biological applications.…”
Section: Frequency-domain Trfcmentioning
confidence: 99%
“…The applications of fluorescence lifetime measurements range significantly. Some examples include separating fluorophores that have similar spectra but different lifetimes [4][5][6][7][8][9][10][11][12][13], exploiting the difference in lifetime of free and bound metabolites for metabolic study and diagnosis [14][15][16][17][18][19][20][21][22][23][24], using FRET to screen for binding or inhibition of exogenous and endogenous molecules of interest [2,5,[25][26][27][28][29][30][31][32][33][34][35], evaluating the conformation and stability of proteins or other molecules in varying environments [31,36], or even using lifetime as an additional parameter in fluorescent inks for anti-counterfeiting [37], though this list is far from exhaustive. New methods and technologies continue to be discovered, further establishing the wide-reaching significance and potential of fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 99%